INFORMATION SEEKING BEHAVIOR OF COASTAL SOCIETY IN SOUTHEAST SULAWESI - Asrul Jaya; Jopang; Ibrahim, Cecep; La Ode Herman; Fera Tri Susilawaty (Literatify: Trends in Library Developments, 2024)
The goal of this study was to discover the information-seeking behaviour of coastal communities in Southeast Sulawesi, which has the second highest marine catch (fish) income in Indonesia, despite the fact that the majority of its territory is made up of oceans, but the people's income is still low and less prosperous, as evidenced by the export value of marine catches still falling under East Java, Jakarta, and South Sulawesi. The data for this study were collected from 105 respondents who used a quantitative technique to fill out a list of information seeking behaviour, while 10 respondents used a qualitative approach, namely in-depth interviews about the hurdles experienced when seeking information. According to the findings of this study, the information seeking behaviour of coastal populations in Southeast Sulawesi is still manual, that is, they still use experiences and feelings by 45.8% of the time, and the barriers they confront in obtaining information are related to technology by 29.1% of the time. The outcomes of the study are directly related to the income obtained by the coastal villages of Southeast Sulawesi, which is still poor and less prosperous